Development of a prototype vegetable slicing machine / Adil Ariff - Ariff, Adil (2023)
Nowadays, there are many people are still using manual cutting vegetable method which is chopping and slicing by using hand knives. This project is to help them to expose more to the technology and make their life easier. The issues that are coming out for this project are the are a lot of works to do by a housewife that need to settle every day, manual chopping or slicing method can be dangerous because our hand are more expose to the sharp part of knives and demand for low price vegetable slicing machine. The objective of this project is to design and analyze a low-cost and small scale machine for housewives and to develop the safety to the machine to avoid injury. This project will be use direct current because it will become a portable machine and use a dc motor that are used to move the cutting blade. The frame for this machine is use aluminium profile to make sure it can be lightweight machine for housewife use everywhere. This machine will be expected to make life easier for housewives